SOL-GEL PROCESS FOR THE MANUFACTURING OF TRANSLUCENT LEAD ZIRCONATE TITANATE GEL-MONOLITH - Silvester Tursiloadi; Hiroaki Imai; Hiroshi Hirashima (Research Center for Chemistry - LIPI, 1996)
Translucent Lead Zirconate Titanate (PZT) gel-monolith was prepared by partially hydrolyzing metal alkoxides solution which modified with acetylacetone(acacH). Metal alkoxides, lead di-i-propoxide, zirconium tetra-nbutoxide and titanium tetra-i-propoxide were used as starting materials. In Infrared spectra for the translucent monolithic gel after aging at room temperature for several days or drying at 90°C for 18h, the most significant feature is the presence of band at around 1554 cm-1 which can be assigned to the v (C-O) and v (C-C) vibrati-ons of acetylacetanate group coordinated to the metal cations Ti and Zr. The diffraction peaks of PbO were found after heating at 300°C for 2h. After heating at 450 °C for 2 h, diffraction peaks of pyrochlore Pb2 Ti206 and perovskite PZT phase were observed. The diffraction peaks of PbO and pyrochlore phase disappeared after heating at 600°C, and tetragonal perovskite phase was stable up to 1000 °C. The diffraction peaks of perovskite phase were also found after heating at 430 ° for 24 h. The density of the compacted pulverizedgel after heating at 1000°C for 30 min. was 6.9 g/cm3 , about 86% of the theoretical value.